Application of Multicultural Aspects in the Development of Exegetical Studies: The Perspective of Tafsir Mafatihul Ghaib by Fakhruddin Ar-Razi - Septiawadi, Septiawadi; Dimas Alan Saputra (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2026)
Abstract The issue of multiculturalism has become increasingly relevant amidst the complexity of diverse global societies, while the Qur’an from the very beginning has embodied the values of equality, tolerance, and respect for differences. Tafsir Mafatihul Ghaib, as a masterpiece of rational-philosophical exegesis, is not only rich in linguistic and theological analysis but also demonstrates openness to various intellectual traditions and socio-cultural contexts. This research employs a library research method with a descriptive-interpretive approach, analyzing thematic verses. The findings reveal that the multicultural aspects from ar-Razi’s perspective include: gender equality, ethnic equality, cultural and religious equality, equality in competition, and recognition of personal character qualities. These aspects can be implemented in the study of Qur’anic exegesis through the development of the following characteristics: equal rights without gender discrimination, unity in ethnic diversity, recognition of the private right to self-determination, acknowledgment of belief as part of multiculturalism, a spirit of competition and sportsmanship, and a logical, scientific culture. In conclusion, Tafsir Mafatihul Ghaib offers an inclusive, tolerant, and moderate model of exegetical study, which is relevant for responding to the dynamics of pluralism in the contemporary era. Keywords: Equality; Fakhruddin ar-Razi; Mafatihul Ghaib; Multiculturalism; Qur’anic Exegesis Studies.   Abstrak Isu multikulturalisme menjadi semakin relevan di tengah kompleksitas masyarakat global yang beragam, sementara Al-Qur’an sejak awal telah mengandung nilai-nilai kesetaraan, toleransi, dan penghargaan terhadap perbedaan. Tafsir Mafatihul Ghaib sebagai salah satu mahakarya tafsir bercorak rasional-filosofis tidak hanya kaya akan analisis kebahasaan dan teologi, tetapi juga menunjukkan keterbukaan terhadap berbagai tradisi pemikiran dan konteks sosial budaya. Penelitian ini menggunakan metode kepustakaan (library research) dengan pendekatan deskriptif interpretative serta menganalisis ayat-ayat tematik. Hasil penelitian menunjukkan bahwa aspek multikultural dalam perspektif ar-Razi meliputi: kesetaraan gender, kesetaraan etnis, kesetaraan budaya dan kepercayaan, kesetaraan kompetisi, serta pengakuan kualitas kepribadian. Aspek-aspek tersebut dapat diimplementasikan dalam pengkajian tafsir melalui pengembangan karakter: persamaan hak tanpa diskriminasi gender, kebersamaan dalam keragaman etnis, pengakuan hak privat kemerdekaan diri, pengakuan keyakinan sebagai bagian dari multikultur, semangat kompetisi dan sportivitas, serta budaya ilmiah yang logis. Kesimpulannya, Tafsir Mafatihul Ghaib menawarkan model pengkajian tafsir yang inklusif, toleran, dan moderat, yang relevan untuk merespons dinamika kemajemukan di era kontemporer. Kata Kunci: Multikulturalisme; Pengkajian Tafsir; Mafatihul Ghaib; Fakhruddin ar-Razi; Kesetaraan.